STUDI EKSPLORASI PROSES PEMBELAJARAN MENULIS KARYA ILMIAH DI PERGURUAN TINGGI - Muhammad Iksan; Adnan; Riadi Suhendra (Jurnal Kependidikan, 2018)
This study aims to obtain a description of the process of learning to write academic papers on the subjects of Academic Writing. This research was descriptive research with subject of 8 lecturers of academic writing and 16 students in 5 institutions of higher education. Data collection was done by using interview technique and document analysis. Testing the validity of data was done by doing crosscheck data between sources and inter-mode. The data analyzed used interactive models by Milles & Huberman. The results showed that from 40 department spread in 5 higher education, only 7 department that program subjects of writing academic. Most of the lecturers did not have the RPS document of Scientific Writing Technique course. Lecturers conducted explanation, discussion, question and answer, and task method in learning. Lecturers did not use scientific and processes approached in learning to write academic papers. Lecturers did use the assessment rubric when correcting student papers. This means that the lecturer did not do the learning on the subjects of Academic Writing Works well.